PERKEMBANGAN BISNIS MODEL KEUANGAN SYRIAH SERTA PENERAPANNYA - Jaka Syahputra (Mount Hope Economic Global Journal, 2023)
Analysing the element of Shariah used as the basis of business, its nature is very universal to the people's artifacts. Eliminating Indonesia's potential as the largest Muslim country in the world. There is a fundamental awareness of the failure of the conventional economic system that has created crises since 1923, 1930, 1940, 1970, 1980, 1990, 1997 even to this day. This qualitative descriptive research uses library studies. The results of the research are that Shari (a compliance) is an important and fundamental element in a Sharia-based financial business. The growth of the multi-faceted sharia-based financial business in Indonesia deserves great appreciation. This is because the element of Shariah used as the basis of business, its nature is very universal to the people's artifacts. Besides, there is a growing fundamental awareness of the failure of the conventional economic system that has created crises since 1923, 1930, 1940, 1970, 1980, 1990, 1997 and even today.